Drug-loaded nano-selenium particles as well as preparation method and application thereof
Through drug-loaded nanoselenium particles technology, nanoselenium particles and tea polysaccharides are used to load doxorubicin hydrochloride and encapsulate it with metal zeolite imidazole framework, which solves the problem of DOX toxic side effects and achieves more efficient drug delivery and tumor killing effects.
Patent Information
- Application Number
- CN202510063534.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
AI Technical Summary
Doxorubicin hydrochloride (DOX) has a variety of toxic side effects in clinical applications, which limits its dosage and efficacy.
Drug-loaded nanoselenium particles are used to load doxorubicin hydrochloride through nanoselenium particles and tea polysaccharides as carriers, and encapsulated with metal zeolite imidazole framework to achieve acid-sensitive targeting effects and sustained release of drugs.
It reduces the toxic side effects of DOX, improves the load and sustained release effect of the drug, and enhances the targeted delivery and killing effect of tumors.
Smart Images

Figure CN119838026A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedicine, and specifically relates to drug-loaded nano-selenium particles and a preparation method and application thereof. Background Art
[0002] Cancer, medically known as malignant tumors, is a general term for a large class of diseases. Its basic characteristic is that the body's cells undergo abnormal genetic changes under the influence of various carcinogenic factors, such as chemicals, physical factors, viruses, etc., which causes the cells to lose normal growth regulation, abnormal proliferation, and may invade surrounding tissues and distant organs, and also metastasize to other parts of the body through the blood or lymphatic system. Primary liver cancer is one of the common malignant tumors. Current studies have found that it may be related to chemical carcinogens and environmental factors such as cirrhosis, viral hepatitis, and aflatoxin. Primary liver cancer mainly includes hepatocellular carcinoma and intrahepatic bile duct carcinoma, among which hepatocellular carcinoma, referred to as HCC, is the main pathological type of liver cancer, accounting for 75% to 85%. In order to treat HCC, global pharmaceutical companies have developed many new drugs. However, treatment-related adverse reactions and low tolerance of patients with liver failure to drug toxicity limit the dosage and efficacy of chemotherapy drugs.
[0003] Doxorubicin hydrochloride, also known as doxorubicin hydrochloride or adriamycin, is widely used in clinical treatment as a broad-spectrum anticancer drug. However, DOX has multiple toxic side effects such as liver and kidney toxicity, inhibition of bone marrow hematopoiesis, delayed cardiac toxicity, and hair loss, which requires strict control of its dosage in actual application to reduce its toxic side effects. Therefore, there is an urgent need to provide a new DOX drug with higher safety. Summary of the invention
[0004] The purpose of the present invention is to provide a drug-loaded nano-selenium particle to reduce the toxic and side effects of DOX during clinical application.
[0005] The technical solution adopted by the present invention is:
[0006] The invention provides a drug-loaded nano-selenium particle. The drug-loaded nano-selenium particle uses nano-selenium particles and tea polysaccharides as carriers to load doxorubicin hydrochloride, and is encapsulated with a metal zeolite imidazole skeleton.
[0007] Preferably, the metal zeolite imidazole framework includes any one of ZIF-8, ZIF-67 and ZIF-90.
[0008] Preferably, the particle size of the nano-selenium particles is 90 nm to 110 nm.
[0009] Preferably, the preparation process of the tea polysaccharide is as follows:
[0010] The tea leaves are crushed and added with water, and the mixture is ultrasonically crushed and heated to collect the filtrate; the protein in the filtrate is removed, the mixture is concentrated, and the precipitate is precipitated with alcohol, and the precipitate is collected, washed, and dried to obtain tea polysaccharides.
[0011] The present invention provides a method for preparing the drug-loaded nano-selenium particles, comprising the following steps:
[0012] Inorganic selenium compounds are reduced to nano-selenium particles, which are then reacted with tea polysaccharides to prepare tea polysaccharide nano-selenium particles; the tea polysaccharide nano-selenium particles are mixed with doxorubicin hydrochloride to prepare tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride; and the tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride are encapsulated with a metal zeolite imidazole skeleton to obtain the drug-loaded nano-selenium particles.
[0013] Preferably, when preparing the tea polysaccharide nano-selenium particles, the molar mass ratio of tea polysaccharide to nano-selenium particles is 100 g to 110 g: 1 mol.
[0014] Preferably, when preparing the tea polysaccharide nano-selenium particles, the molar mass ratio of tea polysaccharide to nano-selenium particles is 100g:1mol.
[0015] Preferably, when preparing the tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride, the mass ratio of the tea polysaccharide nano-selenium particles to doxorubicin hydrochloride is 1:40-50.
[0016] Preferably, when preparing the tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride, the mass ratio of the tea polysaccharide nano-selenium particles to doxorubicin hydrochloride is 1:40.
[0017] Preferably, when preparing the drug-loaded nano-selenium particles, the ratio of the metal zeolite imidazole framework to the tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride is 1 mL: 1 mg to 1.2 mg.
[0018] Preferably, when preparing the drug-loaded nano-selenium particles, the mass volume ratio of the metal zeolite imidazole framework to the tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride is 1 mL:1 mg.
[0019] The present invention also provides an application of the drug-loaded nano-selenium particles, characterized in that the drug-loaded nano-selenium particles are used to prepare a preparation for treating cancer.
[0020] Preferably, the cancer includes any one of liver cancer, stomach cancer, esophageal cancer, lung cancer and kidney cancer.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The invention provides a drug-loaded nano-selenium particle, wherein the drug-loaded nano-selenium particle uses nano-selenium particles and tea polysaccharides as carriers to load doxorubicin hydrochloride, and is encapsulated with a metal zeolite imidazole framework to achieve an acid-sensitive targeting effect. DOX molecules are attached to the surface of the tea polysaccharide nano-selenium particles through physical adsorption, and at the same time, the abundant functional groups on the surface of the tea polysaccharide nano-selenium particles, such as hydroxyl groups, provide adsorption sites for physical adsorption, so that DOX can be loaded onto the particle surface, thereby increasing the loading amount of the drug. When the metal zeolite imidazole framework ZIF-8 is formed, due to its unique porous structure and self-assembly characteristics, the tea polysaccharide nano-selenium particles loaded with DOX are wrapped up to form drug-loaded nano-selenium particles. The nano-selenium particles serve as a carrier of the drug, and ZIF-8 serves as an outer shell, which can protect the internal drug, and the tea polysaccharide nano-selenium particles loaded with DOX can also achieve sustained release and controlled release of the drug through its porous structure. Through the above process, DOX is restricted and modified to reduce the toxic and side effects produced by DOX. In the present invention, the drug-loaded nano-selenium particles are not found to have liver and kidney toxicity, inhibit bone marrow hematopoietic function, delay cardiac toxicity, and cause hair loss.
[0023] Tea polysaccharide is a general term for active polysaccharides extracted from tea leaves. It is another important substance with physiological activity discovered after tea polyphenols. Tea polysaccharide has multiple functions such as lowering blood sugar, lowering blood lipids, lowering blood pressure, anti-cancer, anti-coagulation, and anti-thrombosis. The present invention successfully extracts tea polysaccharide from Yunnan Pu'er tea by water extraction and alcohol precipitation.
[0024] Selenium is a non-metallic chemical element with a very low content in the human body, but it plays an important role in antioxidant, anti-inflammatory and anti-tumor effects. Selenium deficiency usually induces cancer, cardiomyopathy, endocrine system diseases, etc., but excessive supplementation can lead to the occurrence of various diseases such as type 2 diabetes, hair loss and joint pain. Selenium mainly includes three categories: organic selenium, inorganic selenium and elemental selenium. Both organic selenium and inorganic selenium can be absorbed and utilized by the human body, but inorganic selenium usually has the characteristics of easy over-supplementation, poor stability and high toxicity. Organic selenium supplements have become a hot topic in clinical and daily life because of their high efficiency and safety. Compared with organic and inorganic selenium, nano-selenium has superior biocompatibility and drug loading capacity. Nano-selenium elemental SeNPs have a variety of allotropes, the most common of which are amorphous red nano-selenium and black or gray nano-selenium. Amorphous red nano-selenium has higher antioxidant activity and lower toxicity, but amorphous red nano-selenium is unstable and easily aggregates into gray and black nano-selenium. There are many biological templates that can regulate the activity and stability of SeNPs, and sugars, proteins, surfactants, etc. have been used to stabilize SeNPs. These templates contain a large number of hydroxyl, carbonyl and other functional groups, which enable them to interact with SeNPs, thereby avoiding the aggregation and precipitation of SeNPs.
[0025] The metal zeolite imidazole framework has adjustable pore size and large specific surface area, and can adsorb molecules and ions; the structure is not easily destroyed in a certain chemical environment, and can resist the erosion of chemical substances such as acid and alkali, and has good chemical stability; it has low toxicity to organisms and good compatibility in organisms, and is suitable for biomedical fields, such as drug delivery, bioimaging, storage and protection of biomacromolecules, etc. It is also pH-sensitive, and some ZIF materials will undergo structural changes under different pH environments. For example, in the low pH environment of tumor tissue, ZIF-8 may dissociate, achieving sustained release of drugs, and can be used to construct pH-responsive drug delivery systems.
[0026] The present invention uses tea polysaccharides to develop a stable nano-selenium particle, which is used to load the chemotherapy drug doxorubicin hydrochloride, and is encapsulated with a metal zeolite imidazole skeleton to form a synergistic therapeutic effect on tumors. At the same time, the micro-acid in the microenvironment is used to promote the slow release of DOX from the nano-preparation, thereby achieving controlled release of the drug. The present invention achieves better tumor killing effect through nano-selenium carriers without adding chemotherapy drugs, and achieves targeted delivery at the same time.
[0027] The present invention studies and tests the characterization of the drug-loaded nano-selenium particles and their anti-tumor activity in vitro and in vivo. The results show that DTSZ is an irregular particle with an average particle size of 128nm and a zeta potential of 23mV, and can be stably present in a 4°C aqueous environment for more than one week. In vitro experiments and slice results show that DTSZ has good anti-tumor activity and no obvious biological toxicity. In vivo imaging shows that DTSZ has good in vivo targeting. Immunohistochemistry results show that DTSZ can increase the expression level of Caspase-3 protein while reducing the proportion of Ki67-positive cells, thereby achieving the purpose of inhibiting tumor cell proliferation and inducing tumor cell apoptosis. The above research results show that DTSZ is a high-quality tumor treatment drug with potential. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Characterization of drug-loaded nano-selenium particles prepared in Example 1. A is the SEM and TEM images of TS and DTSZ. B is the DLS particle size of TS. C is the DLS particle size of DTSZ. D is the mapping image of DTSZ. E is the potential of TS, DTS, ZIF-8 and DTSZ.
[0029] Figure 2 Characterization and biosafety testing of materials. A is infrared of materials. B is ultraviolet of materials. C is XRD of materials. D is toxicity of materials to HepG2 cells. E is toxicity of materials to L929 cells. F is the release of DTSZ in PBS buffers with different pH values. G is hemolysis test of DTSZ. H is the result statistics corresponding to G. I is the hydrodynamic stability of materials.
[0030] Figure 3 A life-death experiment for materials.
[0031] Figure 4 Results of cell uptake experiments. A shows the uptake of DTSZ by HepG2 cells at different times. B shows the fluorescence intensity of cell uptake at each time period measured by ImageJ software.
[0032] Figure 5 The results of the anti-tumor effect in mice. A shows the changes in the weight of mice during treatment. B shows the sizes of tumors in the Control, DOX, TS, DTS and DTSZ groups from top to bottom. C shows the statistical results of Figure B.
[0033] Figure 6 The following are the H&E and TUNEL fluorescence results of the main organs of mice. A is the H&E section of the main organs of mice. B is the TUNEL fluorescence staining picture of mouse tumors. C is the TUNEL fluorescence intensity measured by ImageJ.
[0034] Figure 7 The following are the results of mouse tumor detection. A is the H&E staining section image of mouse tumor. B is the TUNEL white light staining image of mouse tumor. C is the immunohistochemistry result. D to G are the AST, ALT, CRE and BUN test results of mouse blood, respectively.
[0035] Figure 8 This is a schematic diagram of the preparation of drug-loaded nano-selenium particles in Example 1. DETAILED DESCRIPTION
[0036] The present invention is further described below by specific examples, but the scope of the present invention is not limited thereto. The details and forms of the technical solution of the present invention may be modified or replaced without departing from the spirit and scope of the present invention, but these modifications or replacements all fall within the protection scope of the present invention.
[0037] The inventive concept of the present invention is as follows:
[0038] DOX is a broad-spectrum anticancer drug widely used in clinical treatment. However, DOX has multiple toxic side effects, such as hepatotoxicity, inhibition of bone marrow hematopoiesis, delayed cardiac toxicity, and hair loss. Therefore, in actual application, its dosage needs to be strictly controlled to reduce its toxic side effects. Therefore, there is an urgent need to provide a new DOX drug with higher safety.
[0039] Based on this, the present invention provides a drug-loaded nano-selenium particle, wherein the drug-loaded nano-selenium particle uses nano-selenium particles and tea polysaccharides as carriers to load doxorubicin hydrochloride, and is encapsulated with a metal zeolite imidazole skeleton. DOX molecules are attached to the surface of tea polysaccharide nano-selenium particles by physical adsorption, and at the same time, the abundant functional groups on the surface of tea polysaccharide nano-selenium particles, such as hydroxyl groups, provide adsorption sites for physical adsorption, so that DOX can be loaded on the particle surface, thereby increasing the loading amount of the drug. When the metal zeolite imidazole skeleton ZIF-8 is formed, due to its unique porous structure and self-assembly characteristics, the tea polysaccharide nano-selenium particles loaded with DOX are wrapped up to form drug-loaded nano-selenium particles. Nano-selenium particles serve as carriers of drugs, and ZIF-8 serves as an outer shell, which can protect the internal drugs, and the tea polysaccharide nano-selenium particles loaded with DOX can also achieve sustained release and controlled release of drugs through its porous structure. Through the above process, DOX is restricted and modified, and the toxic and side effects produced by DOX are reduced.
[0040] In order to enable those skilled in the art to better understand the technical solution of the present invention and implement it, the present invention is further described below in conjunction with specific embodiments. In the description of the present invention, unless otherwise specified, the reagents used are all commercially available, and the methods used are all conventional techniques in the art.
[0041] Materials used in the present invention:
[0042] Tea was produced in Yunnan Province, China. Ascorbic acid and sodium selenite were purchased from Sinopharm Chemical Reagent Co., Ltd.; doxorubicin hydrochloride and DMSO were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; 2-methylimidazole was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; fetal bovine serum was purchased from Beijing Solebow Technology Co., Ltd.; DMEM and RPMI-1640 culture media were purchased from Seville; live-death kits were purchased from Bio-Time; and apoptosis kits and CCK-8 were purchased from White Shark Biosharp.
[0043] The abbreviation comparison table of the present invention is shown in Table 1.
[0044] Table 1 Abbreviations
[0045]
[0046]
[0047] Example 1
[0048] A method for preparing drug-loaded nano-selenium particles, the steps are as follows
[0049] S1: Prepare tea polysaccharides as follows:
[0050] Tea polysaccharides were obtained by ultrasonic-assisted hot water extraction, and the specific operation was as follows:
[0051] The tea leaves were crushed and passed through a 40-mesh sieve, deionized water was added, and the mixture was crushed using an ultrasonic cell crusher for 30 minutes. The mixture was placed on a magnetic stirrer and heated at 50°C for 1 hour, and then filtered to obtain a filtrate containing tea polysaccharides. This process was repeated three times, the filtrates were combined, and the protein in the filtrate was removed by Shevager extraction. The mixture was then concentrated by rotary evaporation and alcohol precipitation was performed overnight. The mixture was centrifuged at 4°C and 12,000 rpm, and washed three times. Tea polysaccharides were obtained by vacuum freeze drying, recorded as TPS.
[0052] S2: reducing the inorganic selenium compound to nano-selenium particles, and then mixing with tea polysaccharides to prepare tea polysaccharide nano-selenium particles, the method is as follows:
[0053] 5 mL of 0.01 mol / L sodium selenite and 5 mL of 1 mg / mL tea polysaccharides were mixed and ultrasonicated for 5 min, then 5 mL of 0.04 mol / L L-ascorbic acid was added, and then ultrasonicated for another 5 min and stirred at 500 rpm for 2 h under a magnetic stirrer. After centrifugation at 12000 rpm for 15 min, the supernatant was discarded, and an appropriate amount of deionized water was added for resuspending and centrifuged again. This process was repeated three times to remove residual sodium selenite and L-ascorbic acid. After vacuum freeze-drying for 48 h, tea polysaccharide nano-selenium particles were obtained, which were recorded as TPS-SeNPs, abbreviated as TS.
[0054] S3: Doxorubicin hydrochloride is loaded on the surface of tea polysaccharide nano-selenium particles by physical adsorption and chemical bonding to prepare tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride, the method is as follows:
[0055] Tea polysaccharide nano-selenium was prepared into a 0.5 mg / mL suspension. 2 mg of DOX was accurately weighed, dissolved with 5 μL of DMSO and added to 100 μL of tea polysaccharide nano-selenium. After stirring with a magnetic stirrer at 1200 rpm at room temperature for 24 hours, the precipitate was collected by centrifugation and freeze-dried to obtain tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride, namely DOX / TPS-SeNPs, abbreviated as DTS.
[0056] S4: Encapsulating tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride using a metal zeolite imidazole skeleton to obtain the drug-loaded nano-selenium particles, the method is as follows:
[0057] 0.1 g of zinc nitrate hexahydrate was dissolved in 0.4 mL of deionized water, and 1 g of 2-methylimidazole was dissolved in 4 mL of deionized water to prepare a zinc nitrate hexahydrate solution and a 2-methylimidazole solution.
[0058] Add 100 μL of zinc nitrate hexahydrate solution to a beaker, then add 600 μL of DMSO and 500 μL of 2 mg / mL DTS, add 1 mL of 2-methylimidazole solution after ultrasonication for 5 minutes, and continue ultrasonication for 5 minutes to mix, then stir at 1200 rpm for 1 hour at room temperature under a magnetic stirrer, centrifuge at 12000 rpm for 15 minutes, collect the precipitate, resuspend and centrifuge and wash three times with deionized water, and freeze-dry in vacuum for 48 hours to obtain tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride wrapped in ZIF-8 shell, i.e., drug-loaded nano-selenium particles, denoted as DOX / TPS-Se@ZIF-8, abbreviated as DTSZ. The schematic diagram of the synthesis process of DTSZ is shown in Figure 8 .
[0059] The drug-loaded nano-selenium particles prepared in Example 1 were characterized as follows:
[0060] The morphological characteristics of DTSZ were observed by SEM and TEM, the infrared spectrum of the material was determined by FTIR, the ultraviolet absorption spectrum of the material was determined by UV-visible spectrophotometer, the particle size and Zeta potential of the material were determined by DLS nanoparticle size and Zeta potential analyzer, and the crystal structure of the material was analyzed by X-ray diffractometer.
[0061] (1) In vitro release experiment and stability observation.
[0062] The in vitro release of DTSZ was determined by dialysis. 5 mg of DTSZ was dissolved in 5 mL of PBS buffer at pH 7.4, pH 6.5, and pH 5.5, and added to a dialysis bag with a molecular weight of 3000 Da. The dialysis bags were then placed in beakers containing 50 mL of PBS buffer at the same pH. The beakers were then placed in a shaker at 37°C and 120 rpm. Samples were taken at different time points and the absorbance at 480 nm was measured and recorded by UV-Vis. DTSZ was dispersed in PBS buffer solution and DMEM with 10% FBS added by volume, and the changes in the hydrodynamic size of DTSZ in these two media were observed and recorded.
[0063] (2) Cell culture
[0064] HepG2 and L929 cells were purchased from Haixing Biotechnology. HepG2 was cultured in DMEM, and L929 was cultured in RPMI-1640. DMEM and RPMI-1640 were supplemented with 10% FBS and 1% penicillin-streptomycin, respectively, and placed at 37°C and 5% CO. 2 Culture in an incubator.
[0065] (3) Cytotoxicity assay.
[0066] The CCK-8 kit was used to measure the killing of tumor cells and the toxicity to normal cells by several materials at different concentrations. HepG2 and L929 grown to the logarithmic growth phase were digested and inoculated in a 96-well plate at a density of 5000 per well. After culturing for 24 hours, DTS, DTSZ and DOX were added according to the equivalent DOX concentrations: 0μg / mL, 0.75μg / mL, 1.5μg / mL, 3μg / mL, 6μg / mL, and 12μg / mL, respectively. TS was added in an equal amount to that contained in DTS, and the culture was continued for 12 hours. After the incubation was completed, the culture medium containing the material was aspirated, washed three times with 100μL of PBS, 100μL of basal culture medium containing 10% CCK-8 by volume was added, and after incubation in the incubator for 2 hours, the absorbance of each well at 450nm was measured using an enzyme reader. The cell survival rate was calculated using the following formula:
[0067] OD samples : Absorbance values of wells with culture medium + cells + CCK-8 solution + drug solution.
[0068] OD blank : Absorbance values of wells with culture medium + CCK-8 solution + drug solution and no cells.
[0069] OD 0 : Absorbance values of wells with culture medium + CCK-8 solution and no drug solution.
[0070] (4) Drug loading rate and encapsulation efficiency.
[0071] It can be seen from the UV-visible spectrophotometer that DOX has a characteristic absorption peak at 480nm. DOX solutions of different concentrations were prepared and the absorbance at 480nm was measured respectively. The data were recorded and a DOX standard curve was drawn. The absorbance of the supernatant produced when synthesizing the drug was measured at 480nm by a UV-visible spectrophotometer, and the drug loading rate of DTSZ was obtained by the following formula:
[0072] The encapsulation efficiency of DTSZ can be calculated by the following formula:
[0073] m 1 : Total amount of DOX, mg; m 2 : The mass of DOX contained in the supernatant, mg; m 3 : mass of DTSZ, mg; LC: drug loading rate; EE: encapsulation efficiency.
[0074] (5) Live cell and dead cell staining.
[0075] HepG2 cells grown to the logarithmic growth phase were digested and inoculated into 6-well plates for 24 h. After 24 h, the culture medium was replaced with basal medium and TS, DTS, DTSZ and DOX with an equivalent DOX concentration of 2 μg / mL were added respectively. After addition of the drugs, the cells were incubated for 12 h, washed three times with PBS and stained with Calcein-AM / PI kit. After staining, the results were observed and recorded under an inverted fluorescence microscope.
[0076] (6) Cellular uptake experiment.
[0077] HepG2 cells grown to the logarithmic growth phase were digested and inoculated into 6-well plates for 24 h. DTSZ with an equivalent DOX concentration of 2 μg / mL was used for different treatment times. The culture medium was discarded after 2 h, 4 h, 8 h and 12 h. The cells were washed three times with PBS buffer and fixed with ice methanol for 15 min. After fixation, the cells were stained with DAPI dye and observed and recorded under an inverted fluorescence microscope.
[0078] (7) Tumor-bearing mouse model.
[0079] The experimental animals were purchased from Hangzhou Ziyuan Experimental Animal Technology Co., Ltd. and tested by Hangzhou Medical College and issued with the experimental animal qualification certificate. 6-week-old BALB / c nude mice were injected subcutaneously with 100 μL 1×10 7 HepG2 cells, tumors grow to 100mm 3 The mice were then divided into five groups, and then injected with TS, DTS, DTSZ and DOX at an equivalent DOX concentration of 2.5 mg / kg every other day, and the control group was injected with an equal amount of PBS. During the treatment period, the length (L) and width (W) of the mouse tumor and the weight of the mouse were recorded every day, and the tumor volume was calculated using the following formula:
[0080] V: volume of mouse tumor, cm 3 ; L: length of mouse tumor, in cm; W: width of mouse tumor, in cm.
[0081] (8) Toxicology testing.
[0082] DTSZ was subjected to a hemolysis test. 5 mL of sterile defibrinated sheep blood was taken and 0.2 mL of ethylenediaminetetraacetic acid was added. After treatment, the supernatant was discarded after centrifugation at 1000 rpm. An appropriate amount of PBS buffer was added for washing and centrifugation was performed again until the supernatant was completely clarified. The supernatant was discarded, the lower layer of red blood cells was taken, and the volume was adjusted to 50 mL with PBS buffer to obtain a 2% red blood cell solution. DTSZ was prepared into 100 μg / mL, 200 μg / mL, 300 μg / mL, 400 μg / mL and 500 μg / mL solutions with PBS. 1 mL of sample was mixed evenly with 1 mL of 2% red blood cell solution by volume, and then centrifuged at 2000 rpm for 5 min after standing at 37 ° C for 3 h. The absorbance of the sample at 570 nm was detected by UV-visible spectrophotometer. The positive control was the addition of distilled water, and the negative control was the addition of PBS group. The hemolysis rate formula is as follows:
[0083]
[0084] OD 2 : Absorbance of positive control; OD 0 : Negative control absorbance; OD 1 : Sample absorbance.
[0085] (9) Histology and immunohistochemistry.
[0086] After the treatment, the mice were killed by removing the eyeballs and collecting blood. After the blood was allowed to stand for 1 hour, the blood was centrifuged at 1000 rpm for 15 minutes to obtain serum, and the blood samples were tested for ALT, AST, BUN, CREA and other indicators. The mice were dissected to obtain the heart, liver, spleen, lung, kidney, tumor and other major organs. These organs and tumors were fixed with 4% paraformaldehyde for 48 hours, then embedded in paraffin for H&E staining, TUNEL staining was performed on the tumor, and immunohistochemistry was used to detect the expression of Ki67 and Caspase-3 in tumor tissues.
[0087] The drug-loaded nano-selenium particles prepared in Example 1 were characterized, and the results were as follows:
[0088] (1) Synthesis and characterization of materials.
[0089] The yield of tea polysaccharides obtained by ultrasonic water extraction was 3.17% and the purity was 94.7%. Figure 1It can be seen that TS is a spherical particle with a diameter of about 100nm, and DTSZ is an irregular particle with a diameter of about 150nm. This result is consistent with the DLS result. DTSZ has an obvious core-shell structure. The potentials of TS, DTS, ZIF-8 and DTSZ are -30.36±1.65mV, -25.65±1.36mV, 28.88±4.88mV and 23.13±1.52mV, respectively. This potential change shows that ZIF-8 is successfully wrapped on the surface of DTS. Figure 2 It can be seen from the FTIR spectra of DOX, TS, ZIF-8 and DTSZ that the -1 The characteristic absorption peak of ZIF-8 appears at 1635cm -1 The DOX absorption peak appears at , which is generated by CN vibration. From the peak diagram of DTSZ, it can be seen that DTS is successfully encapsulated in ZIF-8; from the UV-Vis spectra of DOX, TS, DTS, and DTSZ, it can be seen that DTS is successfully encapsulated in ZIF-8; the XRD pattern of TS does not show a sharp crystal peak, which indicates that the TPS-SeNPs generated by the redox reaction system have an amorphous non-crystalline structure. This phenomenon can be attributed to the adsorption of SeNPs on TPS during the formation process, thereby destroying the crystallinity of Se.
[0090] (2) In vitro release experiment and stability.
[0091] The in vitro release curve of DTSZ is shown in Figure 2 As shown, DTSZ was rapidly released in the first 4 h under three pH conditions, with release rates of 10.6%, 57.26% and 68.4% respectively; the release rates at 12 h were 13.9%, 65.7% and 76.81% respectively; after 12 h, the drug was slowly released, and the final release rates at 24 h were 14.7%, 67.8% and 81.97% respectively, proving that DTSZ has a sustained release effect. The hydrodynamic size of DTSZ nanoparticles in PBS buffer solution and DMEM medium with 10% FBS added by volume showed that DTSZ had good stability in these two environments.
[0092] (3) Cytotoxicity assay.
[0093] CCK-8 kit was used to detect the effects of several drugs on HepG2 cell viability and normal L929 cells. Figure 2 It is known that when the equivalent DOX concentration is 3μg / mL, the cell survival rates of the experimental groups added with DTSZ, DTS, TS, and DOX were 19.37%, 16.48%, 63.60%, and 62.89%, respectively. This result shows that DTSZ and DTS have higher HepG2 toxicity than DOX and TS in vitro. Figure 2 It can be seen from E that DTSZ has lower L929 cell toxicity than DTS, TS and DOX at the same equivalent DOX concentration. This result shows that DTSZ has good biocompatibility.
[0094] (4) Drug loading rate and encapsulation efficiency.
[0095] Calculations show that the drug loading rate of DTSZ for DOX is 1.87% and the encapsulation efficiency is 48.75%.
[0096] Live and dead cell staining
[0097] like Figure 3 As shown, at the same equivalent DOX concentration, the proportion of live cells in the experimental group with the addition of DTSZ was less. This experimental result shows that DTSZ has a stronger tumor cell killing effect than simple DOX and TS.
[0098] (5) Cellular uptake experiment.
[0099] like Figure 4 As shown in the figure, at 0h, no DOX fluorescence was observed in HepG2 cells. As the incubation time increased, the fluorescence intensity of DOX in the cells gradually increased and reached the highest at 12h. Flow cytometry showed that as time went on, the fluorescence intensity of DOX in the cells also continued to increase, which was consistent with the results of fluorescence microscopy observation.
[0100] (6) In vivo anti-tumor effect.
[0101] The statistical results of tumor volume and mouse weight showed that Figure 5 As shown, DTSZ has a significant effect in inhibiting tumor growth. During the treatment, the weight of mice is still increasing. This result proves that DTSZ has good biosafety.
[0102] The tissue morphology of the main organs of mice, heart, liver, spleen, lung and kidney, was observed through sectioning. Figure 6 Compared with the control group, no obvious abnormalities were found in the organs of the different experimental groups, which further demonstrated that DTSZ has excellent biosafety. The efficacy of the drug was further analyzed by H&E and TUNEL staining. The results of TUNEL fluorescence staining showed that the DTSZ experimental group had a higher TUNEL positive rate. H&E results showed that DTSZ treatment caused more cell necrosis.
[0103] Figure 7A and B are the results of H&E and TUNEL white light staining of mouse tumors, respectively. The results show that DTSZ has a stronger tumor killing ability than the control group. Ki67 is a nuclear protein related to cell proliferation, and Caspase-3 is the main factor regulating cell apoptosis. Figure 7 As shown in Figure C, the DTSZ treatment group increased the expression level of Caspase-3 protein and reduced the proportion of Ki67 positive cells. This result shows that DTSZ can inhibit cell proliferation and induce cell apoptosis. AST, ALT, CRE, and BUN are related factors in the blood that can reflect the liver and kidney toxicity of organisms. The test results show that none of the treatment groups showed obvious liver and kidney toxicity.
[0104] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0105] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A drug-loaded nano-selenium particle, characterized in that: The drug-loaded nano-selenium particles use nano-selenium particles and tea polysaccharides as carriers to load doxorubicin hydrochloride, and are encapsulated with a metal zeolite imidazole skeleton.
2. The drug-loaded nano-selenium particles according to claim 1, characterized in that: The metal zeolite imidazole framework includes any one of ZIF-8, ZIF-67 and ZIF-90.
3. The drug-loaded nano-selenium particles according to claim 1, characterized in that: The particle size of the nano-selenium particles is 90nm-110nm.
4. The method for preparing drug-loaded nano-selenium particles according to claim 1, characterized in that: The following steps are involved: Reducing the inorganic selenium compound into nano-selenium particles, and then mixing the nano-selenium particles with tea polysaccharides to prepare tea polysaccharide nano-selenium particles; Doxorubicin hydrochloride is loaded on the surface of tea polysaccharide nano-selenium particles by physical adsorption and chemical bonding to prepare tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride; The tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride are encapsulated by using a metal zeolite imidazole skeleton to obtain the drug-loaded nano-selenium particles.
5. The preparation method according to claim 4, characterized in that: When preparing the tea polysaccharide nano-selenium particles, the molar mass ratio of the tea polysaccharide to the nano-selenium particles is 100g-110g:1mol.
6. The preparation method according to claim 4, characterized in that: When preparing the tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride, the mass ratio of the tea polysaccharide nano-selenium particles to doxorubicin hydrochloride is 1:40-50.
7. The preparation method according to claim 4, characterized in that: When preparing the drug-loaded nano-selenium particles, the ratio of the metal zeolite imidazole framework to the tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride is 1 mL: 1 mg to 1.2 mg.
8. The preparation method according to claim 7, characterized in that: When preparing the drug-loaded nano-selenium particles, the ratio of the metal zeolite imidazole framework to the tea polysaccharide nano-selenium particles loaded with doxorubicin hydrochloride is 1 mL:1 mg.
9. The use of drug-loaded nano-selenium particles as claimed in claim 1, characterized in that: The drug-loaded nano-selenium particles are used for preparing a preparation for treating cancer.
10. The use according to claim 9, characterized in that The cancer includes any one of liver cancer, stomach cancer, esophageal cancer, lung cancer and kidney cancer.